2022
DOI: 10.1039/d2dt01102f
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Mn2+ doped ultrathin (n = 2) NPLs and their application in anti-counterfeiting

Abstract: Ultrathin 2D perovskite nanoplatelets (NPLs) have many excellent optical properties including narrow absorption and emission spectra and large exciton binding energies. Doping Mn2+ into perovskite NPLs also introduces strong orange...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…[ 32 ] Specifically, with thickness control at the monolayer level, the large bandgap of perovskite nanoplatelets (NPLs) that induces strong quantum confinement effect can be precisely engineered by changing their thickness. [ 33 ] Nag et al. investigated the Mn 2+ emission in doped 3, 4, and 5 monolayers (ML) CsPbBr 3 NPLs by employing low‐temperature PL measurement, and inferred that their bandgap and energy difference (△) between excitonic recombination and dopant emission enlarged with a decline in the thickness of NPLs.…”
Section: Factors Determining the Optical Behavior In Doped Perovskite...mentioning
confidence: 99%
“…[ 32 ] Specifically, with thickness control at the monolayer level, the large bandgap of perovskite nanoplatelets (NPLs) that induces strong quantum confinement effect can be precisely engineered by changing their thickness. [ 33 ] Nag et al. investigated the Mn 2+ emission in doped 3, 4, and 5 monolayers (ML) CsPbBr 3 NPLs by employing low‐temperature PL measurement, and inferred that their bandgap and energy difference (△) between excitonic recombination and dopant emission enlarged with a decline in the thickness of NPLs.…”
Section: Factors Determining the Optical Behavior In Doped Perovskite...mentioning
confidence: 99%
“…Currently, the newly emerging metal halide perovskite nanocrystals (PNCs), with the advantage of facile synthesis, narrow full width at half maximum, high quantum yields, tunable fluorescence color, and long charge carrier diffusion lengths, have been superior to conventional luminescent material and received glorious development in various fields. [19][20][21][22] Unfortunately, such promising perovskite materials easily tend to degradation under temperature, light, and humidity condition, but on the other side of coin, recent studies have also shown that the intrinsic vulnerability of PNCs toward external environment could also be exploited to design switchable perovskite systems, [23] for example, under suitable external stimuli, perovskites have been successfully applied in smart windows, [24] anti-counterfeiting, [25][26][27][28][29] sensors, [30] and optical data storages. [31] As a new type of stimuli-responsive luminescent materials, the perovskite systems with reversible transition are mainly achieved by chemical and structural transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, information security has imposed a tremendous impact on human living, social stability, and even national security, causing urgent requirements of anticounterfeiting materials and advanced encryption/decryption technologies. [ 1 , 2 , 3 , 4 , 5 , 6 ] To this end, anticounterfeiting materials, including watermarks, [ 7 , 8 , 9 ] photonic crystals, [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] perovskite nanocrystals, [ 20 , 21 , 22 ] and luminescent patterns, [ 23 , 24 , 25 , 26 , 27 , 28 ] have been created to combat threats caused by fake information and information leakage. Versatile stimuli, including pH, light, and chemical and mechanical signals, have been explored as decryption keys to induce changes in appearance and properties of such materials that are visible to naked eyes or verified with special instruments.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1002/advs.202206290 photonic crystals, [10][11][12][13][14][15][16][17][18][19] perovskite nanocrystals, [20][21][22] and luminescent patterns, [23][24][25][26][27][28] have been created to combat threats caused by fake information and information leakage. Versatile stimuli, including pH, light, and chemical and mechanical signals, have been explored as decryption keys to induce changes in appearance and properties of such materials that are visible to naked eyes or verified with special instruments.…”
mentioning
confidence: 99%